Pengembangan E-modul Interaktif Berbasis Tutorial Matakuliah Media Pembelajaran Anak Usia Dini - Muhamad Mukhlason; Dona Tihnike; Siti Maslakhatul Khilmah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This study aims to produce interactive e-module products based on AUD Learning media course tutorials for students of semester V of Piaud Iainu Bangil Study Program which is packaged in e-learning using LMS Moodle. This study uses the research and development method using the Lee and Owens model through five stages, namely: analysis, design, development, implementation, and evaluation. Data collection instruments used include: interviews, observations, questionnaires, and documentation. Data collection techniques are carried out through two events, namely: qualitative descriptive data analysis techniques and statistical data analysis. The results of this study in the form of E-module product feasibility test conducted by material experts and media experts, and conducted through user trials. Validation of e-module products is performed twice. The first validation results from material experts get a percentage of 70% and from media experts get a percentage of 67% of the results can be said to be less feasible to use, so the researchers revised back to the existing materials and media. After the revision, the researchers conducted a second validity test. The second validation results from material experts get a percentage of 91% and from media experts get a percentage of 81% when viewed in terms of eligibility criteria, it is included in the category of very feasible. Furthermore, researchers conducted user trials of 9 students get a percentage of 90% and of 2 lecturers get a percentage of 88% when viewed in terms of eligibility criteria, the e-module product is included in the category of very feasible. From the results of the feasibility test, it has a high potential to be implemented well in the Piaud Iainu Bangil Study Program.